Orthogonal Golay excitation for range side lobe elimination in dual-frequency harmonic imaging. (April 2015) - Shen, Che-Chou; Peng, Jun-Kai; Wu, Chi; Liu, Chia-Yuan
Highlights: Dual-frequency harmonic imaging benefits from improvement of SNR by Golay excitation. Conventional Golay decoding suffers from spectral crosstalk with 3 f 0 and DC interferences. For orthogonal Golay, the output of exchanged filtering can be subtracted from that of the original filtering to remove the crosstalk. Results demonstrate the reduction of range side lobe level in both hydrophone measurement and B-mode imaging. Abstract: Dual-frequency (DF) tissue harmonic imaging has been developed to take advantage of not only harmonic signal at second harmonic (2 f 0 ) frequency but also the inter-modulation harmonic signal at fundamental ( f 0 ) frequency for simultaneous nonlinear detection. Though phase-encoded Golay pair can improve the signal-to-noise ratio of DF harmonic signal at both f 0 and 2 f 0 frequencies, conventional matched filtering cannot correctly decode the crosstalk from harmonic components at DC and third harmonic (3 f 0 ) frequency and will lead to range side lobe artifacts in DF harmonic imaging. For orthogonal Golay pair, however, exchanging the decoding filter will output zero for the signal and keep the crosstalk the same. Therefore, the output of exchanged filtering can be subtracted from that of the original matched filtering to completely remove the spectral crosstalk. Compared to phase inversion method, the proposed orthogonal Golay decoding does not require additional transmits to cancel the unwanted DC and 3 f 0 harmonic interferences and thus the achievable frame rate remains the same. Various experiments have been performed to verify the efficacy of the proposed orthogonal Golay decoding. Results from hydrophone measurements indicate that the proposed method effectively suppresses the spectral overlap between the harmonic signal and the interference. Corresponding range side lobe level (RSLL) can be suppressed by 10–20 dB when the signal bandwidth is 60%. B-mode harmonic imaging also demonstrates a reduction of side lobe magnitude (SLM) by 8 dB at 2 f 0 frequencies.